Targeted mutation of Δ12 and Δ15 desaturase genes in hemp produce major alterations in seed fatty acid composition including a high oleic hemp oil. Issue 5 (10th February 2014) - Bielecka, Monika; Kaminski, Filip; Adams, Ian; Poulson, Helen; Sloan, Raymond; Li, Yi; Larson, Tony R.; Winzer, Thilo; Graham, Ian A.
Summary We used expressed sequence tag library and whole genome sequence mining to identify a suite of putative desaturase genes representing the four main activities required for production of polyunsaturated fatty acids in hemp seed oil. Phylogenetic‐based classification and developing seed transcriptome analysis informed selection for further analysis of one of seven Δ12 desaturases and one of three Δ15 desaturases that we designate CSFAD2A and CSFAD3A, respectively. Heterologous expression of corresponding cDNAs in Saccharomyces cerevisiae showed CSFAD2A to have Δx+3 activity, while CSFAD3A activity was exclusively at the Δ15 position. TILLING of an ethyl methane sulphonate mutagenized population identified multiple alleles including non‐sense mutations in both genes and fatty acid composition of seed oil confirmed these to be the major Δ12 and Δ15 desaturases in developing hemp seed. Following four backcrosses and sibling crosses to achieve homozygosity, csfad2a‐1 was grown in the field and found to produce a 70 molar per cent high oleic acid (18:1Δ9) oil at yields similar to wild type. Cold‐pressed high oleic oil produced fewer volatiles and had a sevenfold increase in shelf life compared to wild type. Two low abundance octadecadienoic acids, 18:2Δ6, 9 and 18:2Δ9, 15, were identified in the high oleic oil, and their presence suggests remaining endogenous desaturase activities utilize the increased levels of oleic acid as substrate. Consistent with this, CSFAD3A produces 18:2Δ9, 15 from endogenous 18:1Δ9 when expressed in S. cerevisiae. This work lays the foundation for the development of additional novel oil varieties in this multipurpose low input crop.